The Role of Classical Sunnī Theology in Islam and Science: Responding to Nidhal Guessoum - Jalajel, David Solomon (Zygon, 2025)
This paper recommends a theological turn for the engagement of Islam and Science. There were two identifiable prior phases. Two broad movements typified the first: an attempt to "Islamise" science, and an attempt to show the Qurʾān miraculously contains modern scientific knowledge. The second phase included non-systematic investigations into methodology, divine action, and some localised issues at the Islam and science interface. Nidhal Guessoum proposes the next step should be developing a theistic interpretation of Islam that conforms with modern science as it stands and harmonises Islamic beliefs with science. This presupposes conflicts or serious tensions between traditional Islamic understandings and modern science. This paper argues that a more rigorous exploration into classical and traditional theological approaches could benefit, as it might reveal possibilities in Islam’s theological traditions that do not result in an inherent tension between Islam and science. For instance, in Sunnī theology, we suggest a default "no-conflict" position can be achieved. Such an approach is recommended, since modern Muslim resistance to science, or to certain scientific theories, is often due to perceptions that science challenges Islamic teachings.